Analysis of Van Hiele's Geometry Thinking Ability in the 5E Learning Cycle Model with Ethnomatematics Nuances in terms of Student Self-efficacy - Wijaya, Teguh Ananta; Zaenuri, Zaenuri; Mariani, Scolastika (Unnes Journal of Mathematics Education Research, 2021)
The purpose of this study is to describe the ability to think geometry in terms of self-efficacy of class VIII SMPIT Assaidiyyah students in 5E Learning Cycle with ethnomatematics nuances. The method in this study uses mixed methods with a concurrent embedded strategy that supports the data obtained from the primary method. In this research, quantitative research is the primary method while qualitative research is the secondary method. The population in this study are all students of class VIII SMPIT Assaidiyyah. Based on the analysis of the description of Van Hiele's geometric thinking skills in terms of student self-efficacy, it is obtained (a) In the category of high Self-efficacy levels, students' geometric thinking skills are at the visualization level, analysis level, and informal deduction level (b) In the category of moderate level of self-efficacy, the level of students' geometric thinking ability is at the visualization level and the analysis level (c) In the low Self-efficacy level category, the geometric thinking ability of students is at the visualization level.